Critical Point Cookies Madu Zinc “Coduzinc” Dalam Hazard Analysis Critical Control Point (HACCP) - Oktavia, Lailatul; Pujianto, Tutut (STIKES dan AKZI Karya Husada Kediri, 2024)
The innovation created by the Student Senate of the Karya Huasada Kediri Nutrition Academy as an effort to overcome stunting is by creating the product Coduzinc (Honey Zinc Cookies). To minimize the incidence of food poisoning cases and identify critical points of product danger, it is necessary to have a quality assurance and food safety system for Coduzinc products, one of which is by using HACCP. The aim of this research is to determine the potential hazards and critical control points of Coduzinc products. The type of research carried out was observational research with the research design being descriptive research. The results of this research show that 2 critical points were found in the Coduzinc raw materials, namely powdered milk and eggs. Based on observation activities during the Coduzinc manufacturing process and HACCP assessment, it can be concluded that the results of identifying potential hazards in Coduzinc products show that physical hazards are the most common potential hazards.